Bacterial srnas: regulation in stress - Chee-Hock Hoe; Carsten A. Raabe; Timofey S. Rozhdestvensky; Thean-Hock Tang (2013)
Bacteria are often exposed to a hostile environment and have developed a plethora of cellular processes in order to survive. A burgeoning list of small non-coding RNAs (sRNAs) has been identified and reported to orchestrate crucial stress responses in bacteria. Among them, cis-encoded sRNA, trans-encoded sRNA, and 5′-untranslated regions (UTRs) of the protein coding sequence are influential in the bacterial response to environmental cues, such as fluctuation of temperature and pH as well as other stress conditions. This review summarizes the role of bacterial sRNAs in modulating selected stress conditions and highlights the alliance between stress response and clustered regularly interspaced short palindromic repeats (CRISPR) in bacterial defense.